Odpowiedź:
Zad. 11
a) [tex](4 * 10^{-6}) * (2 * 10^{-6}) = 8 * 10^{-12}[/tex]
b) [tex](4,8 * 10^{-5}) * (1,25 * 10^{-8}) = 6 * 10^{-13}[/tex]
c) (7 * 10^{-8}) * (8 * 10^{-7}) = 5,6 * 10^{-14}
d) [tex](5,02 * 10^{-7}) * (2.05 * 10^{-8}) = 1,0291 * 10^{-14}\\[/tex]
Zad. 12
a) [tex](4,5 * 10^{8}) * (2 * 10^{-3}) = 9 * 10^{5}[/tex]
b) [tex](8 * 10^{-4}) * (1,5 * 10^{9}) = 1,2* 10^{6}[/tex]
c) [tex](3 * 10^{-10}) * (6*10^{4}) = 1,8 * 10^{-5}[/tex]
d) [tex](1,25 * 10^{10}) *(8*10^{-4}) = 10 * 10^{6}[/tex]
W razie pytań proszę pisać, służę pomocą! <3